Adsorption of ammonium on clinoptilolite in presence of competing cations: Investigation on groundwater remediation. (10th October 2018) - Vocciante, Marco; De Folly D'Auris, Alessandra; Finocchi, Antonio; Tagliabue, Marco; Bellettato, Michela; Ferrucci, Aurelio; Reverberi, Andrea P.; Ferro, Sergio
Abstract: Various civilian, agricultural and industrial activities cause the presence of nitrogen compounds in surface and groundwater, where they are further converted into ammonia and its salts. The progressive increase in ammonium concentration in the environment represents a serious concern since it is one of the main causes of eutrophication and its transformation may lead to carcinogens. On the other hand, wastewater has recently been considered as a potential source of nitrogenous nutrients for plants, once adequate recovery processes have been provided. Among the latter, the adsorption processes must be considered reliable and clean due to the mild operating conditions. An experimental study on the removal of ammonium by adsorption on a zeolite cation exchanger (clinoptilolite mineral) was undertaken, considering the water from an Italian groundwater treatment facility with a treatment capability of 150, 000 L/h. The activity was focused on the polishing step before surface discharge (from 20 mg/L to 5 mg/L, according to restrictions due to neighboring water bodies of naturalistic relevance). The experimental study was part of a wider activity for the evaluation of the performances of a 1000 L/h cation-exchange pilot plant operated at the same industrial site. Thus, the peculiar features of the reported study are ammonium removal until the level of traces, use of a conditioned zeolite, and co-presence of high concentrations of other dissolved cationic species competing for exchange. Graphical abstract: Image Highlights: Ammonium removal by cation exchange has been studied. Adsorption on Clinoptilolite allows reducing the NH4 + content to <20 mg/L. Effectiveness of aged Clinoptilolite has also been assessed. Competitive adsorption of other cations takes place, affecting regeneration as well. Pseudo-second-order and Langmuir equations are adequate for data fitting.